PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL PESERTA DIDIK - Abdullah Abdullah; Muhajir Abd Rahman; Rustina N (IAIN Ambon, 2023)
This study aims to describe and analyze the role of Islamic Religious Education teachers in improving the intellectual intelligence, emotional intelligence and spiritual intelligence of students at SD Negeri 1 and SD Negeri 2 Olas, Huamual District, West Seram Regency. This type of qualitative descriptive research, data collection techniques through observation, interviews and documentation, 6 research informants, 2 teachers and 4 students. Data analysis goes through the stages of data collection, data reduction, data display, data interpretation and drawing conclusions. The results of this study are the role of the Islamic Religious Education teacher in increasing the intellectual intelligence of students which includes planning learning tools, using appropriate methods, giving, evaluating. The role of the Islamic Religious Education teacher on emotional intelligence includes; Islamic Religious Education teachers are able to control students' emotions, train students to be confident through class discussion activities, train students to control their emotions by being social, care about students, help arouse students' enthusiasm for learning, train students to care about the environment. The role of Islamic Religious Education teachers in improving students' spiritual intelligence includes; cooperate with all teachers in the school, instill aqidah (belief) in students to carry out worship, get students used to being grateful for God's blessings, provide examples of discipline, get used to saying greetings, involve students in worship, and implement 5S (smile, greet, greet) , polite, and polite).Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis peran guru Pendidikan Agama Islam dalam meningkatkan kecerdasan intelektual, kecerdasan emosional dan kecerdasan spiritual peserta didik di SD Negeri 1 dan SD Negeri 2 Olas Kecamatan Huamual Kabupaten Seram Bagian Barat. Tipe penelitian deskriptif kualitatif, teknik pengumpulan data melalui observasi, wawancara dan dokumentasi, Informan penelitian sebanyak 6 orang , 2 orang guru dan 4 orang peserta didik. Analisis data melaului tahap pengumpulan data, reduksi data, display data, interpretasi data dan penarikan kesimpulan. Hasil penelitian ini yaitu peran guru Pendidikan Agama Islam dalam meningkatkan kecerdasan intelektual peserta didik meliputi yakni membuat perencanaan perangkat pembelajaran, menggunakan metode yang sesuai, memberikan, melakukan evaluasi. Peran guru Pendidikan Agama Islam terhadap kecerdasan emosional meliputi; Guru Pendidikan Agama Islam mampu mengontrol emosi peserta didik, melatih peserta didik percaya diri melalui kegiatan diskusi kelas, melatih peserta didik mengontrol emosi dengan bersosial, peduli dengan peserta didik, membantu membangkitkan semangat belajar peserta didik, melatih peserta didik peduli dengan lingkungan. Peran guru Pendidikan Agama Islam dalam meningkatkan kecerdasan spiritual peserta didik meliputi; bekerjasama dengan seluruh guru di sekolah, menanamkan aqidah (keyakinan) kepada peserta didik agar melaksanakan ibadah, membiasakan peserta didik mensyukuri nikmat Tuhan, memberikan contoh tentang kedisiplinan, membiasakan mengucap salam, melibatkan peserta didik dalam beribadah, dan menerapkan 5S (senyum, sapa, salam, sopan, dan santun).